Fluorescent glass film as well as preparation method and application thereof
By using a fluorescent glass film mixed with cyan and red phosphor in white LED devices, the problems of reduced efficiency of fluorescence conversion materials and insensitive emission peak wavelength in the prior art are solved, and warm white light emission with high color rendering index and low color temperature are achieved, improving the light output efficiency and light quality.
Patent Information
- Application Number
- CN202411780404.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-07
AI Technical Summary
After long-term use of existing white LED devices, due to the aging of epoxy resin, the efficiency of fluorescence conversion material is reduced, and the emission peak wavelength of CaAlSiN3:Eu2+ is located in the dark red area that is insensitive to the human eye, which cannot effectively achieve warm white light with high color rendering index and low color temperature.
A fluorescent glass film is used, which includes a glass substrate and a fluorescent film coated on the glass substrate. The fluorescent film is made of a mixture of cyan emitter phosphor and red emitter phosphor at a weight ratio of 5 to 20:1, and is prepared by a specific preparation method in combination with the glass powder.
Under the excitation of purple light, the fluorescent glass film can produce warm white light with a high color rendering index and a low color temperature. The color rendering index Ra is at least 90, the color temperature is 4000-4200K, and it improves the light output efficiency and light quality.
Smart Images

Figure CN119569478A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a fluorescent glass film and a preparation method and application thereof. Background Art
[0002] Compared with traditional light sources, white light emitting diodes (white light LEDs) have the advantages of small size, long life, high luminous efficiency, energy saving and environmental protection, and can be widely used in mobile communications, urban landscape lighting, car lights, traffic lights, liquid crystal displays, indoor and outdoor lighting, etc. Although the life of white light LED devices far exceeds that of traditional lighting equipment, such as incandescent lamps and fluorescent lamps, the currently widely used phosphor packaging method for white light LED devices is to use organic silica gel and epoxy resin to directly encapsulate the phosphor on the LED chip.
[0003] CN118389142A discloses a cyan emitting phosphor Ba 1.95 Mg 0.7 Ca 0.3 Si2O7:yEu 2+ The cyan emitting phosphor is mixed with the red phosphor CaAlSiN3:Eu 2+ Encapsulated on a 400nm violet LED chip, high-quality warm white light can be obtained under violet light excitation. The patent document directly encapsulates the phosphor on the LED chip, and requires epoxy resin to be used to encapsulate the phosphor by dispensing. After long-term use of the encapsulated LED, the epoxy resin will age, resulting in reduced efficiency of the fluorescent conversion material. In addition, CaAlSiN3:Eu 2+ The emission peak wavelength is in the deep red region where the human eye is not sensitive.
[0004] In order to solve this problem, technicians in this field began to turn to inorganic packaging materials, such as glass, ceramics, eutectics and single crystals. 3+ There are many studies on single crystals of phosphors, fluorescent glass, glass films and fluorescent ceramics. Fluorescent glass films are the most promising materials for use in the lighting industry because of their high transmittance, easy processing, low cost and strong corrosion resistance.
[0005] CN111003933A discloses a cyan fluorescent glass. The cyan fluorescent glass comprises a glass matrix and cyan fluorescent powder, wherein the cyan fluorescent powder has an emission peak at 485° under blue light excitation. ~ 498nm (Ba 0.95-x Sr x )Si2O2N2:mEu 2+ Cyan oxynitride phosphor. This cyan fluorescent glass can emit ideal cyan light under 460nm blue light excitation, but cannot be used for violet light excitation LED devices.
[0006] CN110993771A discloses a full-spectrum fluorescent glass. The full-spectrum fluorescent glass includes a glass precursor, a green phosphor, a blue phosphor, a cyan phosphor and a red phosphor. The full-spectrum fluorescent glass contains too many types of phosphors. At the same time, when preparing the full-spectrum fluorescent glass, the phosphors need to be divided into two groups and melted with the glass precursor to form a melt, and then the two groups of melts are mixed and heated, and the preparation process is cumbersome and complicated.
[0007] CN112563382A discloses a white light emitting diode structure. The white light emitting diode structure includes an encapsulated colloid containing green phosphor, cyan phosphor and red phosphor, a fluorescent glass containing yttrium aluminum garnet (YAG) phosphor and a blue light emitting diode wafer. The phosphor in the white light emitting diode structure has a continuous and flat spectrum in the visible light band under blue light excitation, and cannot be used for purple light excitation LED devices. Summary of the invention
[0008] In view of this, one object of the present invention is to provide a fluorescent glass film, which can obtain warm white light with a high color rendering index and a low color temperature under ultraviolet light excitation, and has better light output efficiency and light quality. Another object of the present invention is to provide a method for preparing the fluorescent glass film. Another object of the present invention is to provide a use of the fluorescent glass film. Another object of the present invention is to provide a white light LED light source assembly. Another object of the present invention is to provide a white light LED device.
[0009] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.
[0010] In one aspect, the present invention provides a fluorescent glass film, which includes a glass substrate and a fluorescent film coated on the glass substrate; the raw materials of the fluorescent film include fluorescent powder and glass powder, and the fluorescent powder is a mixture of cyan emitting fluorescent powder and red emitting fluorescent powder in a weight ratio of 5 to 20:1;
[0011] The chemical composition of the cyan emitting phosphor is Ba 1.93 Mg 1-x Ca x Si2O7:0.07Eu 2+ , where x is the molar coefficient of Ca, 0.1≤x≤0.9;
[0012] The chemical composition of the red emitting phosphor is (Ca, Sr)AlSiN3:Eu 2+ .
[0013] According to the fluorescent glass film of the present invention, preferably, the weight ratio of the glass powder to the fluorescent powder is 1:1-5.
[0014] According to the fluorescent glass film of the present invention, preferably, the glass substrate is selected from at least one of sapphire, quartz, silicon nitride, PET and ceramic glass.
[0015] According to the fluorescent glass film of the present invention, preferably, the thickness of the glass substrate is 0.1-3 mm.
[0016] On the other hand, the present invention also provides a method for preparing the above fluorescent glass film, comprising the following steps:
[0017] 1) mixing cyan emitting phosphor and red emitting phosphor to obtain mixed phosphor; mixing the mixed phosphor with glass powder to obtain mixed powder; mixing the mixed powder with organic glue to obtain fluorescent film slurry powder; the weight of the organic glue is 1-8wt% of the weight of the mixed powder;
[0018] 2) coating the fluorescent film slurry powder on a glass substrate to form a fluorescent film to obtain coated glass;
[0019] 3) heating the coated glass at 100-150° C. for 5-60 minutes to obtain a pre-sintered fluorescent glass film;
[0020] 4) Sintering the pre-sintered fluorescent glass film at 600-900° C. for 1-30 min to obtain the fluorescent glass film.
[0021] According to the preparation method of the present invention, preferably, the organic sizing material consists of terpene alcohol, alcohol ether ester and C1-C6 alkyl cellulose.
[0022] According to the preparation method of the present invention, preferably, the weight ratio of the terpene alcohol, glycol ether ester and C1-C6 alkyl cellulose is (3-10):(1-3):1.
[0023] On the other hand, the present invention also provides a use of the fluorescent glass film in a white light LED, wherein the fluorescent glass film emits warm white light under the excitation of purple light, has a color rendering index of at least 90, and a color temperature of 4000-4200K.
[0024] On the other hand, the present invention further provides a white light LED light source assembly, comprising the above-mentioned fluorescent glass film and a purple light LED chip.
[0025] In yet another aspect, the present invention further provides a white light LED device, comprising the above-mentioned white light LED light source assembly.
[0026] The fluorescent glass film of the present invention can generate warm white light with a high color rendering index and a low color temperature under the excitation of violet light. The color rendering index Ra of the warm white light is at least 90, and the color temperature is at most 4200K. At the same time, the present invention can obtain better light quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The X-ray diffraction data result diagram of the fluorescent glass film of Example 1;
[0028] Figure 2 The scanning electron microscope results of the fluorescent glass films of Examples 1 to 5 are shown;
[0029] Figure 3 Fluorescence imaging microscope images of the fluorescent glass films of Examples 1 to 5;
[0030] Figure 4 The graphs are result diagrams of steady-state generation spectra and excitation spectra of the fluorescent glass films of Examples 1 to 5;
[0031] Figure 5 The electroluminescence spectrum result diagram of the white light LED device prepared in Experimental Example 1 and the actual image of the white light LED device;
[0032] Figure 6 This is the CIE color coordinate diagram of the white light LED device prepared in Experimental Example 1. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0034] The "color rendering index" mentioned in the present invention refers to an indicator used to measure the ability of a light source to restore the true color of an object, usually denoted as Ra; the value range of the color rendering index is from 0 to 100, and the higher the color rendering index, the stronger the ability of the light source to restore the color of the object.
[0035] The "color temperature" mentioned in the present invention refers to the temperature at which a black body is heated to emit light of the same color as the light emitted by a certain light source. The temperature at which the black body is heated is called the color temperature of the light source, or color temperature for short, and its unit is Kelvin (K).
[0036] The "color coordinates" described in the present invention are a method of representing color coordinates, which are used to determine a point on a chromaticity diagram, which accurately represents the color of the light. The color coordinates are usually composed of two numbers, the horizontal axis is x and the vertical axis is y, and these two numbers represent the position of the color on the chromaticity diagram.
[0037] <Fluorescent glass film>
[0038] The fluorescent glass film of the present invention can be applied to white light LEDs excited by violet light to achieve warm white light with high CRI and low color temperature, and can be applied to the field of solid-state lighting. Compared with the prior art, the fluorescent glass film of the present invention does not require the combined use of multiple color phosphors in obtaining full-spectrum white light. The fluorescent glass film of the present invention only requires the simultaneous use of a cyan-emitting phosphor and a red-emitting phosphor to obtain warm white light with low color temperature, thereby simplifying the components of full-spectrum white light LED devices.
[0039] The fluorescent glass film of the present invention comprises a glass substrate and a fluorescent film coated on the glass substrate. The raw materials of the fluorescent film include fluorescent powder and glass powder. The fluorescent powder is composed of cyan emitting fluorescent powder and red emitting fluorescent powder. The weight ratio of cyan emitting fluorescent powder to red emitting fluorescent powder can be 5 to 20:1; preferably 6 to 18:1; more preferably 8 to 16:1.
[0040] According to one embodiment of the present invention, the chemical composition of the cyan emitting phosphor is Ba 1.93 Mg 1-x Ca x Si2O7:0.07Eu 2+ , wherein x is the molar coefficient of Ca, and 1-x is the molar coefficient of Mg. x may be 0.1≤x≤0.9; preferably 0.2≤x≤0.7; and more preferably 0.3≤x≤0.6.
[0041] According to one embodiment of the present invention, the chemical composition of the red emitting phosphor is (Ca, Sr)AlSiN3:Eu 2+ .
[0042] According to another embodiment of the present invention, the red emitting phosphor (Ca, Sr)AlSiN3:Eu 2+ The emission wavelength is 590-680 nm, preferably 605-630 nm; more preferably, the emission wavelength is 605 nm under violet light excitation. The red emitting phosphor (Ca, Sr)AlSiN3:Eu 2+ It is a red-emitting phosphor with a shorter emission wavelength. Its emission wavelength is in the red area that is sensitive to the human eye and is more easily perceived by the human eye, thereby improving visual clarity and color contrast.
[0043] Reasonable phosphor ratio can ensure that the fluorescent glass film produces warm white light with high rendering index and low color temperature under the excitation of purple light.
[0044] According to one embodiment of the present invention, the weight ratio of the glass powder to the phosphor powder may be 1:1-5; preferably 1:1-4; more preferably 1:1.5-3.
[0045] According to one embodiment of the present invention, the glass powder can be any type of glass powder known in the art, and is not particularly limited herein. For example, it can be commercially available glass powder, preferably SiO2-B2O3-ZnO glass powder.
[0046] According to one embodiment of the present invention, the glass substrate can be selected from at least one of sapphire, quartz, silicon nitride, PET, and ceramic glass; preferably at least one of sapphire, quartz, and silicon nitride; more preferably at least one of sapphire and quartz.
[0047] According to one embodiment of the present invention, preferably, the thickness of the glass substrate may be 0.1 to 3 mm; preferably 0.1 to 1 mm; more preferably 0.1 to 0.5 mm.
[0048] According to another embodiment of the present invention, preferably, the size of the glass substrate may be (5-50)×(5-50)×(0.1-3) mm; preferably (10-45)×(10-45)×(0.1-1) mm; more preferably (15-10)×(15-40)×(0.1-0.5) mm.
[0049] A reasonable ratio of glass powder to phosphor and a reasonable glass substrate are more conducive to improving the luminous intensity and visible light transmittance of the fluorescent glass film.
[0050] <Preparation method>
[0051] The method for preparing the fluorescent glass film comprises a mixing step, a coating step, a pre-sintering step and a sintering step, which will be described in detail below.
[0052] Mixing steps
[0053] The cyan emitting phosphor and the red emitting phosphor are mixed to obtain a mixed phosphor; the mixed phosphor is mixed with glass powder to obtain a mixed powder; the mixed powder is mixed with an organic glue to obtain a fluorescent film slurry powder.
[0054] According to one embodiment of the present invention, the weight of the organic sizing agent may be 1 to 8 wt% of the weight of the mixed powder; preferably 2 to 6 wt%; more preferably 3 to 5 wt%.
[0055] According to one embodiment of the present invention, the organic sizing material is composed of terpene alcohol, glycol ether ester and C1-C6 alkyl cellulose.
[0056] According to another embodiment of the present invention, the weight ratio of terpene alcohol, glycol ether ester and C1-C6 alkyl cellulose can be (3-10):(1-3):1; preferably (3-9):(1-3):1; more preferably (4-8):(1-2):1.
[0057] In the present invention, the terpene alcohol can be selected from at least one of terpineol, vanillyl alcohol, geraniol, sclareol and linalool; preferably at least one of terpineol, vanillyl alcohol and geraniol; more preferably at least one of terpineol and geraniol.
[0058] The glycol ether ester can be selected from at least one of diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, propylene glycol methyl ether acetate, propylene glycol methyl ether propionate, and dipropylene glycol methyl ether acetate; preferably at least one of diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, propylene glycol methyl ether acetate, and propylene glycol methyl ether propionate; more preferably at least one of diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, and propylene glycol methyl ether acetate.
[0059] The C1-C6 alkyl cellulose may be a C1-C5 alkyl cellulose, preferably a C1-C4 alkyl cellulose, and more preferably at least one of methyl cellulose, ethyl cellulose, and n-propyl cellulose.
[0060] Reasonable organic adhesive ratio can ensure that the fluorescent film is more evenly coated on the glass substrate and prevent the fluorescent film from falling off, which is beneficial to improving the luminescent performance of the fluorescent glass film.
[0061] The raw materials used in the present invention can be commercially available products or prepared by existing preparation methods, and are not particularly limited here. The purity of the raw materials of the present invention is at least industrial purity (99.9wt%).
[0062] Coating steps
[0063] The fluorescent film slurry powder is coated on a glass substrate to form a fluorescent film to prepare coated glass.
[0064] In the present invention, coating can be performed using any coating method known in the art, and is not particularly limited herein.
[0065] According to one embodiment of the present invention, fluorescent film slurry powder may be dropped onto a glass substrate and coated using a coating machine to form a fluorescent film.
[0066] According to one embodiment of the present invention, the thickness of the fluorescent film may be 60 to 100 μm, preferably 65 to 95 μm, and more preferably 70 to 90 μm.
[0067] Pre-sintering step
[0068] The coated glass is heated to obtain a pre-sintered fluorescent glass film.
[0069] In the present invention, heating can be performed in any heating device known in the art, and is not particularly limited herein, for example, a high-temperature sintering furnace, a drying oven, and the like.
[0070] According to one embodiment of the present invention, the heating temperature may be 100 to 150°C; preferably 105 to 145°C; more preferably 110 to 140°C.
[0071] According to another embodiment of the present invention, the heating time may be 5 to 60 min, preferably 10 to 50 min, and more preferably 15 to 40 min.
[0072] Reasonable heating conditions are conducive to removing bubbles in the fluorescent film in the coated glass and reducing the adverse effects on the luminous intensity of the fluorescent glass film and the transmittance of visible light.
[0073] In the present invention, the heated product can be cooled after heating to obtain a pre-sintered fluorescent glass film.
[0074] The cooling can be achieved by any cooling method known in the art, and is not particularly limited here. For example, it can be natural cooling or air cooling. Preferably, the temperature is cooled to room temperature (25° C.).
[0075] Sintering steps
[0076] The pre-sintered fluorescent glass film is sintered to obtain the fluorescent glass film.
[0077] In the present invention, sintering can be performed in any sintering device known in the art, and is not particularly limited herein, for example, a high-temperature sintering furnace, a muffle furnace, and the like.
[0078] According to one embodiment of the present invention, the sintering temperature may be 600-900°C; preferably 650-850°C; more preferably 700-800°C.
[0079] According to another embodiment of the present invention, the sintering time may be 1 to 30 min, preferably 3 to 20 min, and more preferably 5 to 15 min.
[0080] Reasonable sintering conditions can improve the luminous intensity and visible light transmittance of the fluorescent glass film, which is conducive to the fluorescent glass film producing warm white light with high rendering index and low color temperature under ultraviolet light excitation.
[0081] In the present invention, the heated product can be cooled after sintering to obtain a fluorescent glass film.
[0082] The cooling can be achieved by any cooling method known in the art, and is not particularly limited here. For example, it can be natural cooling or air cooling. Preferably, the temperature is cooled to room temperature (25° C.).
[0083] <Purpose>
[0084] The present invention also provides the use of the fluorescent glass film in white light LEDs.
[0085] According to one embodiment of the present invention, the fluorescent glass film exhibits warm white light emission under the excitation of purple light, and the color rendering index Ra of the white light can be at least 90; preferably at least 92; more preferably at least 93; the color temperature of the white light can be 4000-4200K; preferably 4020-4190K; more preferably 4050-4180K.
[0086] <White LED light source components>
[0087] The present invention also provides a white light LED light source assembly, comprising the above fluorescent glass film and a purple light LED chip.
[0088] According to one embodiment of the present invention, the wavelength of the purple LED chip may be 380 to 435 nm; preferably 390 to 420 nm; more preferably 395 to 415 nm; and most preferably 400 nm.
[0089] According to another embodiment of the present invention, the purple LED chip is a high-power LED chip, and the power may be 1 to 100 W; preferably 5 to 80 W; more preferably 10 to 50 W.
[0090] <White light LED devices>
[0091] The present invention also provides a white light LED device, comprising the above white light LED light source assembly.
[0092] <Test method>
[0093] XRD determination: The X'Pert PRO XRD powder diffractometer produced by Panalytical was used for the test.
[0094] Scanning electron microscopy measurement: The test was conducted using a Sigma500 field emission scanning electron microscope produced by ZEISS.
[0095] Steady-state emission spectrum measurement: The test was conducted using the FSL1000 steady-state / transient fluorescence spectrometer produced by Edinburgh Instruments.
[0096] Fluorescence imaging measurement: The test was conducted using a FSL1000 steady-state / transient fluorescence spectrometer produced by Edinburgh Instruments coupled to a Nikon Ni-U-Olympus BX53 Micro-PL system.
[0097] Electroluminescence spectrum measurement: PCE-2000A photoelectric color comprehensive test system produced by Hangzhou Yuanfang Optoelectronic Information Co., Ltd. was used.
[0098] Color rendering index determination: PCE-2000A photoelectric color comprehensive testing system produced by Hangzhou Yuanfang Photoelectric Information Co., Ltd. was used.
[0099] <Ingredients>
[0100] Unless otherwise specified, the raw materials in the following examples are all commercially available products. Among them, SiO2-B2O3-ZnO glass powder was purchased from Chizhou Fuhua Powder Technology Co., Ltd.
[0101] Example 1
[0102] Preparation of fluorescent glass film:
[0103] The cyan emitting phosphor Ba 1.93 Mg 0.6 Ca 0.4 Si2O7:0.07Eu 2+ and red emitting phosphor (Ca,Sr)AlSiN3:Eu 2+ The mixed phosphor is mixed in a weight ratio of 8:1 to obtain a mixed phosphor; the mixed phosphor is mixed with SiO2-B2O3-ZnO glass powder in a weight ratio of 3:2 to obtain a mixed powder; the mixed powder is mixed with an organic adhesive accounting for 3wt% of the weight of the mixed powder to obtain a fluorescent film slurry powder; the organic adhesive is prepared by mixing pinene alcohol, diethylene glycol butyl ether acetate and ethyl cellulose in a weight ratio of 5:1:1.
[0104] The fluorescent film slurry powder was coated on a 30×30×3 mm sapphire substrate using a coating machine to form a fluorescent film with a coating thickness of 80 μm, thereby obtaining a coated glass;
[0105] The coated glass was placed in a drying oven, heated at 120°C for 20 minutes to remove bubbles, and then cooled to room temperature (25°C) to obtain a pre-sintered fluorescent glass film.
[0106] The pre-sintered fluorescent glass film was placed in a muffle furnace and sintered at 750° C. for 10 minutes to obtain the fluorescent glass film.
[0107] The X-ray diffraction data of the fluorescent glass film prepared in this embodiment is shown in Figure 1 , wherein Example 1 represents the fluorescent glass film prepared in Example 1. ;
[0108] The scanning electron microscopy results are shown in Figure 2 The fluorescence microscopy results are shown in Figure 3 .
[0109] Steady-state emission spectrum Figure 4 .
[0110] Depend on Figure 2 It can be seen that the surface of the fluorescent glass film is relatively smooth and has no obvious cracks.
[0111] Depend on Figure 3 It can be seen that the cyan phosphor and the red phosphor are dispersed more evenly in the fluorescent glass film.
[0112] Depend on Figure 4 It can be seen that as the cyan-red ratio gradually increases, the red light emission intensity gradually decreases, and the emission spectrum of the fluorescent glass film covers 480 to 700 nm, with a wide spectral emission range.
[0113] Example 2
[0114] The only difference from Example 1 is that the ratio of cyan emitting phosphor to red emitting phosphor is different, that is, the cyan-red ratio is different. The cyan-red ratio of the fluorescent glass film in this example is 10:1.
[0115] The scanning electron microscopy results of the obtained fluorescent glass film are shown in Figure 2 The fluorescence microscopy results are shown in Figure 3 The steady-state emission spectrum results are shown in Figure 4 .
[0116] Example 3
[0117] The only difference from Example 1 is that the cyan to red ratio is different. The cyan to red ratio of the fluorescent glass film in this example is 12:1.
[0118] The scanning electron microscopy results of the obtained fluorescent glass film are shown in Figure 2 The fluorescence microscopy results are shown in Figure 3 The steady-state emission spectrum results are shown in Figure 4 .
[0119] Example 4
[0120] The only difference from Example 1 is that the cyan to red ratio is different. The cyan to red ratio of the fluorescent glass film of this embodiment is 14:1.
[0121] The scanning electron microscopy results of the obtained fluorescent glass film are shown in Figure 2 The fluorescence microscopy results are shown in Figure 3 The steady-state emission spectrum results are shown in Figure 4 .
[0122] Example 5
[0123] The only difference from Example 1 is that the cyan to red ratio is different. The cyan to red ratio of the fluorescent glass film of this embodiment is 16:1.
[0124] The scanning electron microscopy results of the obtained fluorescent glass film are shown in Figure 2 The fluorescence microscopy results are shown in Figure 3 The steady-state emission spectrum results are shown in Figure 4 .
[0125] Application Experiment Example 1
[0126] The fluorescent glass film prepared in Example 1 was encapsulated on a 20W high-power 400nm purple LED chip to prepare a white light LED light source assembly, and a full-spectrum white light LED device was prepared using the white light LED light source assembly. Under the excitation of the 400nm purple LED chip, the fluorescent glass film exhibited warm white light emission, and full-spectrum white light LED lighting could be achieved.
[0127] The electroluminescence spectrum and color rendering index of the full-spectrum white light LED device were measured, and the results are shown in Figure 5 and Figure 6 .
[0128] like Figure 5 and Figure 6 As shown in the figure, under the condition of 400nm violet light excitation, the electroluminescence spectrum of the fluorescent glass film shows ultra-broadband emission. Figure 5 The actual luminescence diagram of the visible LED device. By coupling the fluorescent glass film of Example 1 with a purple LED chip (wavelength of 400nm), high-quality warm white light is obtained, and the color rendering index Ra of the warm white light is 93.9, the color temperature is 4163K, and the color coordinates are (0.3760, 0.3823). It can be seen that the fluorescent glass film of the present invention can achieve ultra-wide spectrum coverage, thereby obtaining warm white light with high color rendering index and low color temperature.
[0129] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A fluorescent glass film, characterized in that: The fluorescent glass film comprises a glass substrate and a fluorescent film coated on the glass substrate; the raw materials of the fluorescent film comprise fluorescent powder and glass powder, and the fluorescent powder is a mixture of cyan emitting fluorescent powder and red emitting fluorescent powder in a weight ratio of 5 to 20:1; The chemical composition of the cyan emitting phosphor is Ba 1.93 Mg 1-x Ca x Si2O7:0.07Eu 2+ , where x is the molar coefficient of Ca, 0.1≤x≤0.9; The chemical composition of the red emitting phosphor is (Ca, Sr)AlSiN3:Eu 2+ .
2. The fluorescent glass film according to claim 1, characterized in that: The weight ratio of the glass powder to the phosphor is 1:1-5.
3. The fluorescent glass film according to claim 1, characterized in that: The glass substrate is selected from at least one of sapphire, quartz, silicon nitride, PET, and ceramic glass.
4. The fluorescent glass film according to claim 1, characterized in that: The thickness of the glass substrate is 0.1-3 mm.
5. A method for preparing the fluorescent glass film according to any one of claims 1 to 4, comprising the following steps: 1) mixing cyan emitting phosphor and red emitting phosphor to obtain mixed phosphor; mixing the mixed phosphor with glass powder to obtain mixed powder; mixing the mixed powder with organic glue to obtain fluorescent film slurry powder; wherein the weight of the organic glue is 1-8wt% of the weight of the mixed powder; 2) coating the fluorescent film slurry powder on a glass substrate to form a fluorescent film to obtain coated glass; 3) heating the coated glass at 100-150° C. for 5-60 minutes to obtain a pre-sintered fluorescent glass film; 4) Sintering the pre-sintered fluorescent glass film at 600-900° C. for 1-30 min to obtain the fluorescent glass film.
6. The preparation method according to claim 5, characterized in that: The organic sizing material consists of terpene alcohol, diol ether ester and C1-C6 alkyl cellulose.
7. The preparation method according to claim 6, characterized in that: The weight ratio of the terpene alcohol, the glycol ether ester and the C1-C6 alkyl cellulose is (3-10):(1-3):
1.
8. Use of the fluorescent glass film according to any one of claims 1 to 4 in a white light LED, characterized in that: The fluorescent glass film emits warm white light under the excitation of purple light, the color rendering index of the white light is at least 90, and the color temperature of the white light is 4000-4200K.
9. A white light LED light source assembly, characterized in that: The white light LED light source assembly comprises the fluorescent glass film as claimed in any one of claims 1 to 4 and a purple light LED chip.
10. A white light LED device, characterized in that: The white light LED device comprises the white light LED light source assembly according to claim 9.
Citation Information
Patent Citations
Full-spectrum fluorescent glass, preparation method thereof, packaging heat dissipation structure and LED lamp
CN110993771A
Cyan fluorescent glass, preparation method thereof and full-spectrum LED device thereof
CN111003933A
White light emitting diode structure and manufacturing method thereof
CN112563382A
Cyan emitting fluorescent powder as well as preparation method and application thereof
CN118389142A